Composition and Structure of Phosphate-Rich Parietal Crusts and Nodules in Monte Corchia Cave, Alpi Apuane (Central Italy) - Piccini, Leonardo; Nannoni, Alessia; Costagliola, Pilario; Paolieri, Mario; Vigiani, Chiara (Frontiers in Earth Science, 2021)
Cave environment allows long-term processes of rock weathering and chemical deposition that cannot occur on Earth surface directly exposed to meteoric and external biochemical agents. Apart from the common carbonate speleothems, chemical precipitation from infiltration water can also produce phosphate-rich formations usually occurring as parietal dark crusts or spheroidal nodules. Despite the potential purposes of these kind of deposits as paleoenvironmental proxies, they have been still poorly investigated by cave scientists. Monte Corchia cave (NW Tuscany, Central Italy) is one of the most studied caves in the world, particularly for paleoclimate reconstructions from calcite speleothems. Several samples of parietal formations were collected in relict phreatic and epiphreatic passages at different altitudinal levels that reflect different evolution stages of this large cave system. Samples were analyzed by diffractometry and SEM-EDS possibly revealing the occurrence of hydroxyapatite or fluorapatite mixed with Fe/Mn incrustations and allogenic clastic particles. Crusts often cover the entire section of relict phreatic or epiphreatic passages and can be related to precipitation during waterfilled phases. Phosphate nodules are almost entirely composed by hydroxyapatite or fluoroapatite and could be the result of long-term chemical (or bio-chemical) precipitation in air-filled environments.